Trade‐offs affect the adaptive value of plasticity: stronger cannibal‐induced defenses incur greater costs in toad larvae. Issue 1 (20th November 2020) - DeVore, Jayna L.; Crossland, Michael R.; Shine, Richard
Abstract: Adaptive developmental plasticity allows individuals to match their phenotype with their environment, increasing fitness where threats are inconsistently present. However, despite clear advantages of plasticity, adaptive traits are not ubiquitously nor infinitely plastic. Trade‐offs between benefits and costs or limits are therefore theoretically necessary to constrain the evolution of plastic responses. Systems in which extreme risk can be reliably detected are ideal for investigating trade‐offs, as even costly responses may be adaptive where risk is severe. Cane toads ( Rhinella marina ) are abundant in Australia and produce large clutches (frequently >10, 000 eggs), but asynchronous breeding and rapid development result in variable larval densities within breeding pools. In the field, we found that cannibalism by older cohorts often reduces the survival of conspecific eggs and newly hatched pre‐feeding larvae ("hatchlings") by >99%, as feeding larvae ("tadpoles") use chemical cues from the relatively immobile hatchlings to locate and consume them. After hatchlings become free‐swimming, however, they cannot be cannibalized. Hatchlings can reduce this period of vulnerability by accelerating development when they detect cannibal cues. However, this developmental acceleration decreases initial tadpole mass, reduces subsequent survival, growth, and development, affects behavior, and compromises feeding structures. Reaction norms differ among clutches, and greater developmental acceleration is followed by greater impairment of larval function in plastic clutches, whereas nonresponsive clutches are unaffected by cue exposure. More plastic clutches ultimately exhibit both poorer performance and greater variation among siblings in exposed and (to a lesser degree) control treatments. Variation among clutches in tadpole viability is driven by differences in plasticity rather than phenotype; fitness reductions are linked to developmental acceleration, not rapid development per se. Clutches with intrinsically slow pre‐feeding developmental rates exhibit stronger acceleration (i.e., steeper reaction norms), but clutches with intrinsically rapid development reach invulnerable stages more quickly than those that accelerate development. As a result, high cannibalism risk may favor canalized rapid development rather than facultative developmental acceleration. Cannibalism plays an important role in the recruitment of this invasive species, and hatchling defenses against this threat demonstrate how the limits and costs associated with an inducible defense can favor canalized defenses over phenotypic plasticity.